2021
DOI: 10.1096/fj.202002559r
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles regulate purinergic signaling and epithelial sodium channel expression in renal collecting duct cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…EVs from the culture medium of wild type and Pkd1 -/- mDCT15 and mIMCD3 cells were isolated by ultracentrifugation as described previously ( 20 , 32 ). Briefly, cells were plated in 8 T-175 flasks (1.2x10 6 cells/flask for mDCT15 cells and 1.4x10 6 cells/flask for mIMCD3 cells).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs from the culture medium of wild type and Pkd1 -/- mDCT15 and mIMCD3 cells were isolated by ultracentrifugation as described previously ( 20 , 32 ). Briefly, cells were plated in 8 T-175 flasks (1.2x10 6 cells/flask for mDCT15 cells and 1.4x10 6 cells/flask for mIMCD3 cells).…”
Section: Methodsmentioning
confidence: 99%
“…Extracellular vesicles (EVs) represent a heterogenous family of lipid vesicles carrying several cellular components (e.g., lipids, nucleic acids, proteins), which play an essential role in cell-to-cell communication. In the kidney, EVs have been shown to mediate proximal-to-distal communication and, in this way, regulate electrolyte transport ( 20 ). EVs comprise microvesicles and exosomes, which arise from the outward budding of the plasma membrane as well as from the endosomal compartment, respectively ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, given the role of EVs in intercellular communication, EVs may mediate regulation between tubular segments (Figure 4). In vitro studies have demonstrated that proximal tubular EVs modify the activity of the epithelial sodium channel (ENaC) in the distal nephron [95], [96]. Similarly, EVs isolated from engineered proximal tubule cells were shown to improve the functional maturation of "tubuloids" (organoids showing a predominant tubular phenotype) including enhanced transport capacity of organic anion transporter 1 (OAT1) [97].…”
Section: Evs In Tubular Function and Diseasementioning
confidence: 99%
“…The copyright holder for this this version posted February 9, 2022. ; https://doi.org/10.1101/2022.02.08.479621 doi: bioRxiv preprint strategy in regulating kidney regeneration [24,25]. These vesicles are nanosized lipid bilayer structures that mediate cellular communication through the transfer of bioactive molecules, including proteins, nucleic acids and lipids [26]. Based on biogenesis, size and content, EVs can be classified as exosomes (30 -150 nm), microvesicles (100 nm -1 μm) and apoptotic bodies (50 nm -5 μm), presenting different biological functions based on their cargo [27].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, urinary EVs isolated from rats and from conditioned medium (CM) of proximal tubule cells contain functionally active aquaporin 2 (AQP2), which can be transferred to other tubular epithelial cells [24,25]. EVs secreted by human kidney proximal tubule cells were also shown to modulate the regulation of purinergic signaling in collecting duct cells through increased extracellular ATP and downregulation of epithelial sodium channel (ENaC) [26]. Moreover, CM and isolated EVs from kidney epithelial cells were capable of inducing mesenchymal cells to acquire a more epithelial phenotype [28][29][30].…”
Section: Introductionmentioning
confidence: 99%